Morphological observation and molecular phylogeny of Spirometra decipiens complex 1 (Cestoda: Diphyllobothriidae) found in cat from Chile. (April 2022) - Fredes, Fernando; Mercado, Rubén; Salas, Ismael Pereira; Sugiyama, Hiromu; Kobayashi, Hirotaka; Yamasaki, Hiroshi
Abstract: The systematics of tapeworms in the genus Spirometra has been progressing with the accumulation of molecular genetics data, but the taxonomic status of many nominal species remains under debate. We report morphological and molecular-phylogenetic data for a Spirometra species collected from a domestic cat ( Felis silvestris catus ) in Chiloé Island, Chile. The Spirometra species was shown to be genetically conspecific with Spirometra decipiens complex 1 found in a Pampas fox ( Lycalopex gymnocercus ) from Argentina, and was closely related to a Hoary fox ( Lycalopex vetulus ) and rattlesnake ( Crotalus durissus ) from Brazil. Therefore, the presence of S. decipiens complex 1 was molecularly confirmed for the first time in Chile. The findings of the present study add useful information for the systematics of poorly known Spirometra species in South America. Graphical abstract: Unlabelled Image Highlights: Adult worm of Spirometra species was found in a domestic cat from Chile. Molecular data of the specimen confirmed its assignment to Spirometra decipiens complex 1. S. decipiens  complex 1 occurs widely distributed in South America. Cat also serves as the definitive host as well as Pampas fox and Hoary fox.